2000
DOI: 10.1002/(sici)1096-9861(20000424)420:1<127::aid-cne9>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Projection of the marginal shell of the anteroventral cochlear nucleus to olivocochlear neurons in the cat

Abstract: The marginal shell of the anteroventral cochlear nucleus is anatomically and physiologically different from its central core. Previous studies suggest that neurons in the marginal shell are well suited to encode the intensity of acoustic stimuli. To investigate the projections of the marginal shell, a focal injection (<100 nl) of a mixture of biotinylated dextran amine (BDA) and 3H‐leucine was made into the marginal shell of the cat combined with injection of cholera toxin subunit‐B (CTB) into the cochleas. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 48 publications
4
70
0
Order By: Relevance
“…The small cell cap is emerging as a nexus of auditory brainstem regulatory pathways. Neurons that reside there are components of circuits that control the middle ear reflex (Billig et al 2007) and cochlear output (Ye et al 2000). The small cell cap is the preferred target of the collateral projections of medial olivocochlear neurons (Liberman and Brown 1986;Brown et al 1988;Benson et al 1996), whose principal role is to modulate cochlear gain via their innervation of outer hair cells.…”
Section: Functional Considerationsmentioning
confidence: 99%
“…The small cell cap is emerging as a nexus of auditory brainstem regulatory pathways. Neurons that reside there are components of circuits that control the middle ear reflex (Billig et al 2007) and cochlear output (Ye et al 2000). The small cell cap is the preferred target of the collateral projections of medial olivocochlear neurons (Liberman and Brown 1986;Brown et al 1988;Benson et al 1996), whose principal role is to modulate cochlear gain via their innervation of outer hair cells.…”
Section: Functional Considerationsmentioning
confidence: 99%
“…In contrast, projections from PVCN to MOC neurons have been suggested by fiber degeneration studies (Warr, 1969) and further clarified by tracer experiments (Thompson and Thompson, 1991). Other tracer studies have shown that neurons in the AVCN marginal shell also project to MOC neurons (Ye et al, 2000). Physiological studies are necessary to determine the respective roles of these different pathways in the MOC reflex circuitry and to determine whether other CN areas may also be involved.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Facilitation may have been missed, though, because our contralateral effect is small and variable. Such facilitation may be generated by a very different reflex pathway, possibly from the marginal shell of AVCN (Ye et al, 2000). Schematic of medial olivocochlear (MOC) reflex pathways that can affect cochlear responses from the ipsilateral (right) ear.…”
Section: Monaural Reflexes and Binaural Facilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflexive inputs from the cochlear nucleus (CN) drive the MOC neuron's response to sound (Warr 1969;Thompson et al 1991;Liberman and Guinan 1998;Ye et al 2000;Brown et al 2003). LOC neurons also receive CN inputs but their sound-evoked responses have not been determined.…”
Section: Introductionmentioning
confidence: 99%